Kurikulum Merdeka: Transformasi Pembelajaran yang Relevan, Sederhana, dan Fleksibel - Prisca Regina Putri Novia Rani; Maduki Asbari; Vincensius Dandi Ananta; Ilham Alim (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to support the development of students' potential through the Independent Curriculum which is designed so that the learning system becomes more relevant, simple, and flexible by following the changing times. In this study report using a descriptive qualitative method by taking notes because the source of the data obtained by listening to oral narration from the BSKAP Youtube channel of the Ministry of Education and Culture entitled "Podcast Sapa Pendidikan, Curriculum Merdeka: Relevant, Deep, and Fun" presented by Drs. Zulfikri Anas, M.Ed. The results of this study explain that the education system must continue to follow the changing times, Curriculum changes are very important to ensure that the education provided remains relevant to the demands of the times. This research began with many parties who have a mindset and concept of "Change ministers, change the curriculum". Such a perspective can change the mindset of society which causes society to become anti-change. This must be assured by providing full socialization to the community that this change brings happiness and luck so that the community has a good view of the independent curriculum.